The technological specialization of Europe in the 1990s - Federico Foders (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
This paper contributes to the ongoing debate on the international position of Europe by (i) presenting new evidence on technological specialization and competitiveness and (ii) exploring methodological issues underlying the empirical analysis. The results show that the technological profile of the member countries of the European Union offers a wide scope for technology transfer and inter-industry trade both within the European Union and between the member countries of the European Union on the one hand and Japan, the United States and Eastern Europe on the other. However, risks loom large in the possible eastward enlargement of the European Union and in the formation of a monetary union, because of the former's and the latter's potential impact on the European Union's technological profile and the international competitiveness of European firms.
Keywords: 330; Technologie; Hochtechnologiesektor; Internationale Arbeitsteilung; Internationaler Wettbewerb; Industriegüteraußenhandel; EU-Staaten